Prakiurusios pepsinės opos Baltarusijoje: praeitis ir dabartis - Lobankov, Vladimir M. (Lietuvos chirurgija, 2006)
Perforated peptic ulcers in Belarus: past and presentVladimir M. LobankovDepartment of Hospital Surgery,Gomel State Medical University,Lange str. 5, 246000 Gomel, BelarusE-mail: lobankov1959@mail.ruObjectiveThe monitoring of perforated peptic ulcer incidence in Belarus is reviewed for the years 1960–2004.MethodsThe review of the annual incidence of perforated peptic ulcers during 1960–2004 is based on the official statistics of the Belorussian Ministry of Public Health. The index of perforated ulcer incidence per 100,000 population has been derived, with the account of population changes during these years.ResultsMild variations of these statistics were observed before the 90s with an insignifcant tendency to grow from the second half of the 70s to the first half of the 80s. The Chernobyl accident in 1986 was not followed by any response. The incidence of perforated peptic ulcers almost doubled in the first half of the 90s, regional differences in the statistics appeared. These changes coincided with the collapse of the USSR and deterioration of the living standards. Hence, the socioeconomic factor has a dominating influence governing the risk of peptic ulcer complications, perforations in particular.ConclusionThe author emphasizes the need to promote the role of public prophylaxis and definite preventive surgery for the patients with a severe ulcer evolution.Key words: perforated peptic ulcer, incidence